2022
DOI: 10.1097/pcc.0000000000003038
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Tranexamic Acid in Major Pediatric Trauma Within a Physician-Led Emergency Medical Services System: A Multicenter Retrospective Study

Abstract: Describe prehospital tranexamic acid (TXA) use and appropriateness within a major trauma pediatric population, and identify the factors associated with its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Although the IDF CPG uses a lower weight-based dose of TXA for children, there were significant discrepancies from age-adjusted doses of TXA in the current study, as 74% of our pediatric patients received “adult” TXA doses of 1000 mg, which is a deviation from the CPG. Amaury et al (7) also reported that most pediatric patients received a 1,000 mg loading dose of TXA in the prehospital setting, aligning with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the IDF CPG uses a lower weight-based dose of TXA for children, there were significant discrepancies from age-adjusted doses of TXA in the current study, as 74% of our pediatric patients received “adult” TXA doses of 1000 mg, which is a deviation from the CPG. Amaury et al (7) also reported that most pediatric patients received a 1,000 mg loading dose of TXA in the prehospital setting, aligning with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence supporting the administration of TXA in children therefore remains limited, with most studies focusing on feasibility and safety in this population (22). Amaury et al (7) recently described use of TXA in a prehospital registry, reporting its use in up to a third of major pediatric trauma, with inconsistencies in adherence to clinical indications. In a nontraumatic setting, Schertz et al (23) demonstrated that the use of antifibrinolytics, including TXA, was effective in reducing blood products requirements in children undergoing cardiac surgery with cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reply: W e thank Cazes et al (1) for their insightful remarks on our work by Gossiome et al (2) published in Pediatric Critical Care Medicine. One concern was whether dispatched mobile medical teams (MMTs) were staffed by adult or pediatric emergency physicians.…”
mentioning
confidence: 93%
“…Despite its widespread availability (75%), respondents in a recent European survey of helicopter emergency medical services reported using it in only 15% of patients (3), far less than what was reported in our study (1) (40.0% of the cohort). The last point that has been raised by Cazes et al (1) questioned the need for further research to validate the use of TXA in children with severe trauma and argued that studies reporting safe use and efficacy in minimizing blood loss may be sufficient to generalize the use of TXA in trauma cases. However, most of studies were conducted in specific surgical settings and no randomized control trial has ever been conducted to rigorously validate TXA use in other pediatric settings.…”
mentioning
confidence: 99%